110 Patient acceptability of telephone follow up after cataract surgery. (16th November 2020) - Khavandi, Sarah; Lim, Ernest; Mole, Guy
Abstract : GM and EL are both employees of Ufonia Ltd a company funded by Innovate UK that specialises in automating routine healthcare using natural language processing over the telephone. Aims: Healthcare is often slow to adopt innovation due to difficulties in changing culture and attitudes towards technological alternatives. This study aimed to evaluate the patient acceptability of a novel method for providing cataract follow up over the telephone (TFU) by looking at multiple factors of acceptability. This methodology can be used as a reproducible framework to guide co-development of future technology such as automated artificial-intelligence (AI) enabled TFU. Methods: Patients between the ages of 66 and 90 were called 3 weeks after their surgery by an ophthalmologist to assess if they had symptoms that could indicate a complication and require face-to-face review. We interviewed 30 consecutive patients who had received TFU within the last month. Patient acceptability was assessed through the validated Telehealth Usability Questionnaire (TUQ) and the likert scale responses were analysed. Qualitative data was collected through a semi structured questionnaire and a Braun and Clarke (2006) method of thematic analysis was carried out. Results: The majority of patients found that TFU post cataract operation was an acceptable way to receive follow up. On average patients scored 4.94/5 on the likert scale for the simplicity and ease of use. Overarching themes that emerged were that TFU is more desirable as it saves time, travel and NHS resources. Overall, patients felt that if they had a postoperative complication they would have preferred to have seen a clinician in person. We found patients' views influenced by the COVID-19 pandemic meaning they saw additional benefits of telephone follow up compared to face-to-face review. Conclusions: The majority of patients felt that TFU after cataract surgery was an acceptable way to receive healthcare. This has implications for how follow up is provided after the most common operation in the UK and worldwide and opens the possibility of this being provided by an automated AI driven system in the future.